1995
DOI: 10.1007/bf01740763
|View full text |Cite
|
Sign up to set email alerts
|

Is sepsis a mediator-inhibitor mismatch?

Abstract: vation appears to precede that of the cellular system, but the sequence of this release of mediators is not well known. In sepsis, however, endotoxins [or lipopolysaccharides (LPS)] or other bacterial toxins seem to be the triggering mechanisms for the acute inflammatory response. Both sepsis and SIRS are the consequence of an excessive host response uncontrolled by natural inhibitors, and certain complications, such as organ dysfunction and shock, are frequently seen after both sepsis and SIRS, when hypotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 51 publications
0
10
0
3
Order By: Relevance
“…During sepsis, cascades of inflammatory response mediate various cardiovascular dysfunctions, including vascular endothelial cell damage, vascular permeabilization, vasodilatation, hypotension, and myocardial depression (36). Persistently high levels of serum IL-6 reportedly predict high mortality in septic patients (1,(37)(38)(39). Therefore, augmented induction of IL-1␤, IL-6, and ICAM-1 in aged mouse hearts may be causally associated with the high mortality rate of aged mice during endotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During sepsis, cascades of inflammatory response mediate various cardiovascular dysfunctions, including vascular endothelial cell damage, vascular permeabilization, vasodilatation, hypotension, and myocardial depression (36). Persistently high levels of serum IL-6 reportedly predict high mortality in septic patients (1,(37)(38)(39). Therefore, augmented induction of IL-1␤, IL-6, and ICAM-1 in aged mouse hearts may be causally associated with the high mortality rate of aged mice during endotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Upon infection with Gramnegative bacteria, released endotoxin (e.g. lipopolysaccharide, LPS) 1 stimulates monocytes/macrophages to produce such initial proinflammatory cytokines as tumor necrosis factor ␣ (TNF␣) and interleukin 1␤ (IL-1␤). These two in turn elicit a subsequent release of secondary inflammatory mediators, including inducible nitric-oxide synthase (iNOS), intracellular adhesion molecule-1 (ICAM-1), and IL-6 (1).…”
mentioning
confidence: 99%
“…It has been suggested that the pro-infl ammatory response is necessary during the septic process, since it triggers the activation of microbicidal mechanisms, while an excessive anti-infl ammatory response could lead to a state of immunoparalysis [47]. It is also clear that the anti-infl ammatory response is necessary to regulate the exacerbated pro-infl ammatory response that is triggered during sepsis, since if the former does not appear there is a risk of activating mechanisms leading to multiple organ dysfunction [26].…”
Section: Discussionmentioning
confidence: 99%
“…In physiological conditions, it is considered as a main mediator of events involved in infl ammation and immunity [8], playing a preponderant role in defense against infections by fungi [9,10], bacteria [11][12][13][14] and even parasites [15]. Paradoxically, its exacerbated production during the septic process, together with the presence of other cytokines like IL-1b, IL-12, IL-8 and IFNg [16][17][18][19][20][21][22][23][24][25], contri butes to the development of tissue damage and multiple organ dysfunction [26]. This occurs through such mechanisms as overproduction of nitric oxide, with the consequent decrease in peripheral vascular resistance [27] which facilitates extracellular extravasation of liquids, activation of the coagulation cascade associated with the development of disseminated intravascular coagulation [28] and the migration of PMN to zones of infl ammation with subsequent degranulation and direct tissue damage [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, evidence continues to accumulate implicating numerous biochemical participants included in the collective "septic cascade"; which if not controlled ultimately lead to multiple organ failure [1][2][3][4]. The use of suitable anti-microbial medicines, even if they eliminate the microorganisms that triggered the septic process, often will not be enough to prevent the host's worsening and dying [5].…”
mentioning
confidence: 99%